2021
DOI: 10.1021/acs.joc.1c01361
|View full text |Cite
|
Sign up to set email alerts
|

Photocycloadditions of Arenes Derived from Lignin

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Photochemical cycloadditions of lignin‐derived phenol compounds with alkenes ( 86 , Scheme 6) can also be considered to be driven by ESAA relief of the S 1 state benzene ring with the formation of photochemically more stable structure [179] . Under irradiation, vanillin carrying an alkene side chain can undergo intramolecular [2+2] photocycloaddition to form a nonaromatic tricyclic product 87 .…”
Section: Relief Of Esaamentioning
confidence: 99%
“…Photochemical cycloadditions of lignin‐derived phenol compounds with alkenes ( 86 , Scheme 6) can also be considered to be driven by ESAA relief of the S 1 state benzene ring with the formation of photochemically more stable structure [179] . Under irradiation, vanillin carrying an alkene side chain can undergo intramolecular [2+2] photocycloaddition to form a nonaromatic tricyclic product 87 .…”
Section: Relief Of Esaamentioning
confidence: 99%
“…Our recent results give new insights on the nature of the excited state involved in the first step of ortho photocycloaddition of benzonitrile derivatives (Scheme 13). [57] The irradiation of benzonitrile derivative 45 bearing a methoxy substituent revealed that the singlet excited state prevails by direct absorption in acetonitrile. On the one hand, the major products 46 and 47 are the result of a singlet state meta photocycloaddition.…”
Section: E-cd Complexmentioning
confidence: 99%
“…Such studies have also been performed in the context of the sustainable production of vanillin [ 90 , 91 ]. In the context of organic photochemical reactions, for example cycloaddition with alkenes, derivatives of this compound are particularly interesting because in such transformations a high degree of molecular complexity and diversity is generated without chemical activation and thus reducing waste production [ 27 , 92 , 93 , 94 ].…”
Section: Photocatalytic Transformations Of Biopolymersmentioning
confidence: 99%